2010
DOI: 10.1095/biolreprod.109.078329
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Oviduct and Demonstration of Epithelial Fate Determination in Mice1

Abstract: The mouse oviductal epithelium is a simple monolayer until Postnatal Day 7 and subsequently consists of differentiated secretory cells and ciliated cells. In adult oviduct, the two types of epithelial cells are unevenly distributed; ciliated cells are dominant in the ampulla and secretory cells are dominant in the isthmus. Recombinants of enzymatically separated epithelial and mesenchymal tissues of oviducts were grafted under kidney capsule for 4 wk. The recombinants developed structures with a lumen covered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 26 publications
3
41
1
2
Order By: Relevance
“…Our recent study (31) and the present study showed that the fate of oviductal epithelial cells is determined around P3-P5. Therefore, Fstl1 must be expressed during this period.…”
Section: Further Screening Of Mesenchymal Factors Identified By Sst Msupporting
confidence: 67%
See 3 more Smart Citations
“…Our recent study (31) and the present study showed that the fate of oviductal epithelial cells is determined around P3-P5. Therefore, Fstl1 must be expressed during this period.…”
Section: Further Screening Of Mesenchymal Factors Identified By Sst Msupporting
confidence: 67%
“…Our recent study has revealed that undetermined epithelial cells coexist with cilial and secretory epithelial cells in perinatal oviducts (31), suggesting that epithelial fate-determining mechanisms become activated around postnatal days 3-5 (P3-P5). Accordingly, clonal epithelial cell lines E1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…About 80 percent of epithelial cells are ciliated in the infundibulum (Agduhr, 1927;Stewart and Behringer, 2012;Yamanouchi et al, 2010), which is the region close to the open end of the oviduct. Although the myosalpinx contractions also play roles in the transportation of ova, the ciliary movements at the infundibulum are sufficient to generate oviductal flow and to carry the oocytes towards the uterus (Halbert et al, 1989;Halbert et al, 1976;Shi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%